2011
DOI: 10.1016/j.foodchem.2010.09.099
|View full text |Cite
|
Sign up to set email alerts
|

Assay of the antioxidant capacity of foods using an iron(II)-catalysed lipid peroxidation model for greater nutritional relevance

Abstract: The formation of free radicals by the iron-catalysed Fenton reaction is a major cause of oxidative damage in the body. Here a common assay of antioxidant capacity, inhibition of the β-carotene-linoleic acid model of lipid peroxidation, has been modified by the addition of ferrous iron (final concentration 36 µmol/l), which makes the rate of oxidation of the lipids occur twenty-five times faster. Such an assay can simulate the oxidative damage to membrane lipids and low density lipoproteins occurring in the bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The strong iron (II) chelating activity we observe for MH may result from one or more of the antibacterial phenolics present in MH (Weston et al ). Iron‐chelating activity has been attributed to the phenolic fraction of Beech Honeydew honey from New Zealand, but the exact molecules responsible have yet to be identified (Brangoulo and Molan ). Like MH, Beech Honeydew honey has been shown to have high levels of non‐peroxide antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%
“…The strong iron (II) chelating activity we observe for MH may result from one or more of the antibacterial phenolics present in MH (Weston et al ). Iron‐chelating activity has been attributed to the phenolic fraction of Beech Honeydew honey from New Zealand, but the exact molecules responsible have yet to be identified (Brangoulo and Molan ). Like MH, Beech Honeydew honey has been shown to have high levels of non‐peroxide antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%
“…The free radical scavenging activity was determined according to the method of Baltrusaityte et al [ 57 ] with some modifications reported by Brangoulo et al [ 58 ]. The ABTS•+ free radical solution was prepared (final concentration-7 mM/L) with potassium persulphate (final concentration-2.45 mM/L) and left to react for 16 h to form the stable ABTS•+ radical cation.…”
Section: Methodsmentioning
confidence: 99%
“…Each assay was carried out in triplicate. This method follows closely that used by previous workers [16]. The inhibitory activity was calculated as for the DPPH assay.…”
Section: Abts Radical Scavenging Assaymentioning
confidence: 99%